Do we need an anti-oligarchic constitution? - Bagg, S (SAGE Publications, 2021)
Camila Vergara’s Systemic Corruption is an extraordinarily rich, provocative and original work of political theory, which makes several compelling interventions in the normative literature. It develops a forceful critique of overly narrow definitions of corruption, insisting that a more ‘systemic’ conception is required in order to grasp the scale of oligarchic domination in contemporary democracies. It also points out the limitations of the ‘proceduralist’ model of contestation adopted by neo-republicans, and outlines a persuasive conception of the people as a partisan actor with specific interests to defend. Yet Vergara’s alternative vision of how popular power might be institutionalized is less convincing. Though she rightly insists on the importance of organized countervailing power and plebeian solidarity, the system of nested local assemblies that she proposes is not well-suited to foster the development of either.